Step
*
4
1
of Lemma
arctangent-rleq
1. x : ℝ
2. r0 ≤ x
3. ∀x:ℝ. (r0 < (r1 + x^2))
4. ∀y:{x:ℝ| x ∈ [r0, ∞)} . ((r0 ≤ y) 
⇒ ((r0 - arctangent(r0)) ≤ (y - arctangent(y))))
5. (r0 - arctangent(r0)) ≤ (x - arctangent(x))
⊢ arctangent(x) ≤ x
BY
{ (RWO "arctangent0" (-1) THEN Auto) }
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  r0  \mleq{}  x
3.  \mforall{}x:\mBbbR{}.  (r0  <  (r1  +  x\^{}2))
4.  \mforall{}y:\{x:\mBbbR{}|  x  \mmember{}  [r0,  \minfty{})\}  .  ((r0  \mleq{}  y)  {}\mRightarrow{}  ((r0  -  arctangent(r0))  \mleq{}  (y  -  arctangent(y))))
5.  (r0  -  arctangent(r0))  \mleq{}  (x  -  arctangent(x))
\mvdash{}  arctangent(x)  \mleq{}  x
By
Latex:
(RWO  "arctangent0"  (-1)  THEN  Auto)
Home
Index